ECCENTRIC HAMSTRING STRENGTH IS ASSOCIATED WITH AGE AND DURATION OF PREVIOUS SEASON HAMSTRING INJURY IN MALE SOCCER PLAYERS - Vicens-Bordas, Jordi (Int J Sports Phys Ther, 2020)
BACKGROUND: Eccentric hamstring strength seems important in reducing the odds of future hamstring injuries. While age and previous injury are well-known risk factors for future hamstring injuries, the association of age and previous hamstring injury with eccentric hamstring strength in the following season is unknown. PURPOSE: To investigate the association of age and previous hamstring injury with preseason eccentric hamstring strength in soccer players, and to investigate the association between previous hamstring injury duration and preseason eccentric hamstring strength. STUDY DESIGN: Descriptive, cross-sectional study METHODS: A convenience sample of 284 male amateur soccer players (age 18-38 years) was included in the analyses. Self-reported information about previous season hamstring injury and its duration (three weeks or less; more than three weeks) was collected. Preseason eccentric hamstring strength was obtained during the Nordic hamstring exercise using a field-based device. RESULTS: Age had a negative association with preseason eccentric hamstring strength with 0.9% reduction per year. Players with a previous hamstring injury duration of more than three weeks (n=27) had 13% lower preseason eccentric hamstring strength compared to players without previous hamstring injury. CONCLUSION: Older players have lower preseason eccentric hamstring strength than younger players. Players with a previous hamstring injury duration of more than three weeks have lower preseason eccentric hamstring strength than the rest of the players. These results highlight the need to monitor and address the identified weaknesses in eccentric hamstring strength in amateur soccer players, with specific emphasis on older players with a previous hamstring injury of longer duration. LEVEL OF EVIDENCE: 2b